DAN MYELOPEROxIDASE) DAN DISFUNGSI ENDOTEL (ASIMETRIK DIMETILARGININ) DI KEGEMUKAN (OBESITAS) - Joko Widodo; Burhanuddin Bahar; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Obesity is a pathological condition in which there is an excess body fat due to imbalance energy expenditure. Its association with oxidative stress could cause other metabolic disorders such as endothelial dysfunction, atherosclerosis, and cardiovascular disease. Theaim of this study was to assess the correlation of oxidative stress (F2-Isoprostane, Superoxide dismutase and Myeloperoxidase) andendothelial dysfunction (Asymmetric dimethylarginine) which happened in central obese men. A cross sectional study was carried outin 62 central obesity male subjects with ages range between 30−60 years. The researcher determined SOD activity, concentration ofMPO as well as ADMA. In this study was found a significant correlation of F2-Isoprostan (r = 0.333, p = 0.008), MPO (r = 0.386; p = 0.008) and ADMA but not with SOD. The elevated concentration of F2-Isoprostane occur 3.5 times (p = 0.02; 95%; CI = 1.19–10.19), elevated MPO occur 3.7 times (p = 0.023; 95%; CI = 1.16–11.56) while combination of elevated F2-Isoprostane-MPO occur6.7 times (p = 0.011; 95%; CI = 1.33-33.24) will increase the risk of endothelial dysfunction. There was a significant correlation of oxidative stress with endothelial dysfunction, and the increase concentration of F2-Isoprostane and MPO indicates the occurrence of endothelial dysfunction in central obesity.